Sustainability Performance Management Integration: A Systemic Approach In Improving The Organizational Competitiveness Of PT. Sentosa Deli Mandiri - Nst, Venny Fraya Hartin; Wijaya, Doly Muhendy; Azaman, Azaman; Nasti, Nilawati (Universitas Ibn Khladun Bogor, 2025)
This research examines the integration between performance management and sustainability as a systemic approach in improving organizational competitiveness, with a case study at PT Sentosa Deli Mandiri. The main problem analyzed is the effectiveness of implementing sustainable performance management strategies in supporting the company's long-term goals. A descriptive qualitative approach was used with data collection techniques in the form of in-depth interviews, participatory observation, and documentation studies. The results showed that the integration of economic, social, and environmental indicators into the performance measurement system is able to encourage operational efficiency, improve reputation, and corporate accountability. The Sustainability Balanced Scorecard (SBSC) model proved relevant as a strategic framework in aligning sustainability goals with organizational performance. This finding confirms that a systemic approach is an important foundation in building a long-term sustainable competitive advantage